Randomized comparative trial of efficacy of paracetamol, ibuprofen and paracetamol-ibuprofen combination for treatment of febrile children - Vyas, Falgun Indravadan (Medknow Publications & Media Pvt Ltd, 2014)
OBJECTIVE: Paracetamol and ibuprofen are widely used for fever in children as monotherapy and as combined therapy. None of the treatments is proven clearly superior to others. Hence, the study was planned to compare the efficacy of paracetamol, ibuprofen and paracetamol-ibuprofen combination for treatment of febrile children. MATERIALS AND METHODS: This was an investigator blind, randomized, comparative, parallel clinical trial conducted in 99 febrile children, 6 months to 12 years of age, allocated to three groups. First group received paracetamol 15 mg/kg, second group received ibuprofen 10 mg/kg and third group received both paracetamol and ibuprofen, all as a single dose by the oral route. Patients were followed-up at intervals of 1, 2, 3 and 4 h post dose by tympanic thermometry. RESULTS: Mean tympanic temperature after 4 h of drug administration was significantly lower in the combination group compared with paracetamol group (P < 0.05); however, the difference was not clinically significant (<1°C). The rate of fall of temperature was highest in the combination group. Number of afebrile children any time post dose until 4 h was highest in the combination group. Difference between combination and paracetamol was significant for the 1(st) h (P = 0.04). Highest fall of temperature was noted in the 1(st) h of drug administration in all the groups. No serious adverse events were observed in any of the groups. CONCLUSION: Paracetamol and ibuprofen combination caused quicker temperature reduction than either paracetamol or ibuprofen alone. If quicker reduction of body temperature is the desired goal of therapy, the use of combination of paracetamol + ibuprofen may be advocated.